2000
DOI: 10.1046/j.1442-9993.2000.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Flowering phenology of myrtaceous trees and their relation to climatic, environmental and disturbance variables in northern New South Wales

Abstract: Patterns of flowering phenology, which represent a partial description of food availability for nectarivores, are described for 20 species of myrtaceous trees on the mid‐north coast of New South Wales (NSW), Australia. Data were recorded monthly between 1982 and 1992 across 23 sites that comprise a variety of local environmental conditions and disturbance histories. Flowering periodicity and intensity were highly variable between species and sites, ranging from annual flowering to no flowering over the 10‐year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(69 citation statements)
references
References 44 publications
0
69
0
Order By: Relevance
“…Eby -2007, may drive HeV spillover events. Finally, nectar and fruit availability are dependent on climatic conditions (Law et al 2000), and thus flying foxes-particularly the highly nectardependent LRFF-may be greatly affected by climate change. Our data suggest that such environmental stresses lead directly to changes in henipavirus infection and excretion dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Eby -2007, may drive HeV spillover events. Finally, nectar and fruit availability are dependent on climatic conditions (Law et al 2000), and thus flying foxes-particularly the highly nectardependent LRFF-may be greatly affected by climate change. Our data suggest that such environmental stresses lead directly to changes in henipavirus infection and excretion dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations of translocated trees representing this region in the Bonalbo trial indicated that they took 20-21 months to develop, which was notably longer than the translocated CCV from the northern subtropical zone, but appeared to be in accord with the duration between initiation and anthesis for more southerly native populations of CCV (i.e. 15-24 months; Law et al 2000). Similar congruence in the key floral-development phases was evident for translocated and native CM (Table 2).…”
Section: Correspondence In Floral Development Between Translocated Anmentioning
confidence: 66%
“…The November census time was chosen to commence monitoring because this was before the previously recorded anthesis period for spotted gums in northern NSW (Law et al 2000; Table 2). …”
Section: Annual Flowering Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sanewski (2010) observed that S. luehmannii flowered massively in the first spell and showed minor flowering in the second spell after unseasonal heavy rainfall in spring in southeast Queensland, Australia and attributed such a flowering response to the prevailing temperature and water availability (Sanewski 2010). Law et al (2000) reported that high rainfall in summer-autumn period resulted in heavy flowering in spring for most of the Myrtaceae members. Keatley et al (2002) reported a significant relationship between temperature and rainfall and flowering in eucalypts over 23 years.…”
mentioning
confidence: 99%